2022
DOI: 10.3389/fonc.2022.841276
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Venetoclax and Midostaurin Efficiently Suppressed Relapsed t(8;21)Acute Myeloid Leukemia With Mutant KIT After Failure of Venetoclax Plus Azacitidine Treatment

Abstract: Acute myeloid leukemia (AML) with t(8;21) is categorized as favorable-risk AML, but KIT mutations show a significantly poor prognostic impact in such patients. Persistent vulnerability to relapse is a major challenge in the treatment of this subtype of patients. Venetoclax is a BCL-2 selective inhibitor. The venetoclax+HMA strategy is also a notable salvage regimen that achieves good clinical outcomes in the treatment of relapsed or refractory (R/R) AML. However, in our clinical practice, we found that disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…In a multicenter, phase 2 trial of VEN + azacitidine plus homoharringtonine in R/R AML, 6 patients with t(8;21) were included, and all achieved remission after treatment [ 12 ]. Similarly, we recently reported that midostaurin showed synergistic effects with VEN in an ex vivo study, and the combination therapy rescued two relapsed t(8;21) AML patients with KIT mutations who progressed rapidly after VEN + azacitidine therapy [ 13 ].…”
mentioning
confidence: 88%
“…In a multicenter, phase 2 trial of VEN + azacitidine plus homoharringtonine in R/R AML, 6 patients with t(8;21) were included, and all achieved remission after treatment [ 12 ]. Similarly, we recently reported that midostaurin showed synergistic effects with VEN in an ex vivo study, and the combination therapy rescued two relapsed t(8;21) AML patients with KIT mutations who progressed rapidly after VEN + azacitidine therapy [ 13 ].…”
mentioning
confidence: 88%
“…While epigenetic modifiers azactidine and decitabine have been shown to be growth inhibitory in KIT‐mutant mast cell leukaemia cell lines [37], D816V‐mutant KIT has been associated with progression on midostaurin and azacitidine combination treatment in a patient with systemic mastocytosis [38]. Disease progression on venetoclax and azacitidine therapy was also reported for two AML patients with tyrosine kinase domain KIT mutations [39]. Thus, mutant KIT may be associated with poor response to these hypomethylating therapies.…”
Section: Dataset Briefmentioning
confidence: 99%
“…Gilteritinib and quizartinib were approved for relapsed/refractory (R/R) AML patients with FLT3 mutation in 2018 and 2019, respectively [ 16 , 17 ]. In addition to FLT3, other receptor tyrosine kinases (RTKs) like KIT are targets of RTK inhibitors such as midostaurin, sorafenib, dasatinib, and bemcentinib [ 18 , 19 ]. Besides, the inhibitors of IDH2 (enasidenib) and IDH1 (ivosidenib) were also approved for the treatment of R/R AML with corresponding mutants in 2017 and 2018, respectively [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%